COMPARISON OF TWO INVASIVE NON-SURGICAL TREATMENT OPTIONS FOR UTERINE MYOMAS: UTERINE ARTERY EMBOLIZATION AND MAGNETIC RESONANCE GUIDED HIGH INTENSITY FOCUSED ULTRASOUND— SYSTEMATIC REVIEW - Yerezhepbayeva, Madina; Terzic, Milan; Aimagambetova, Gulzhanat; Crape, Byron (BMC Women’s Health, 2022)
Background: Uterine Artery Embolization (UAE) and Magnetic Resonance guided High Intensity Focused Ultrasound (MRgHIFU) are two noninvasive treatments for uterine leiomyoma. Methods: This systematic review, following PRISMA guidelines, analyzed the efectiveness of two treatments by comparing percent fbroid volume shrinkage immediately after the procedure and after 3, 6, 12 and 24 months of follow-up and also assessed and compared common complications following treatment. The search utilized Science Direct, PubMed, MEDLINE, Google Scholar and BioMed Central databases, selecting manuscripts published during the period 2000 and 2020. Studies with premenopausal patients with previous treatments for uterine leiomyoma and/or with other pelvic diseases were excluded. Results: Twenty-nine papers satisfed inclusion and exclusion criteria. Results were pooled and stratifed by treatment and follow-up time. Weighted fbroid volume percent shrinkage after UAE was statistically signifcantly greater than MRgHIFU at 6, 12, and 24 months follow-up times. However, UAE had statistically signifcantly more complications, such as pain, nausea and vomiting. However, this study cannot conclude that UAE is more efective than MRgHIFU due to confounding factors.
Keywords: Type of access: Open Access; Magnetic resonance guided high intensity focused ultrasound; Uterine artery embolization; Uterine leiomyoma; Uterine fbroid